DETERMINATION OF PHENOL IN WATER USING PHENOL SENSOR - Aulia Ayuning Tyas; Zuhrotul Aini; Wulan Sekilas Wari (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2015)
The aim of the research was to study the effect of ionophore concentration, membrane thickness, and pH solution in sensor performance and its application to sample. Method of the research used phenol sensor that can be made by coating Screen Printed Carbon Electrode (SPCE) with ionophore CTAPh (Cethyltrimethylammonium phenoxide) in chitosan membrane.This research used various ionophore concentration (0.5%; 1.0%; 1.5%; 2.0%; and 2.5%), membrane thickness (60µm, 80µm, 100µm, 110µm) and pH solution (9, 10, 11, 12). The research showed that the best phenol sensor performance at 1.5%, 60µm membrane thickness and pH solution 11. The research also showed that the best phenol sensor has 60 seconds response time, the Nernstian factor is 54.437mV/dekade, concentration range between 10-8-10-5 M (0,001-1ppm). Phenol sensor can be used to determine phenol in water which lower than limit detection of standard method.